(untitled) (Academia Science Repository, 2023)
The article examines how the introduction of digital technologies is changing the banking landscape in Uzbekistan. It discusses the level of adoption of digital financial services such as mobile banking and online payments, their impact on traditional banking services, and the challenges and opportunities they present for financial inclusion. The article also examines emerging trends and trends in the digital financial services landscape and their impact on the banking sector and the wider economy in the coming years.